LITERATURE REVIEW ANALYSIS ON THE INFLUENCE OF FINANCIAL MANAGEMENT PRACTICES ON CORPORATE PERFORMANCE AND FINANCIAL RESILIENCE IN THE ERA OF DIGITAL TRANSFORMATION - Sudarsono; Bernadetta Anita Jerry S; Benhur Pakpahan; Jasa Ginting; Sabarita Tarigan (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2026)
This study aims to analyze the influence of financial management practices on corporate performance and financial resilience in the era of digital transformation using a Systematic Literature Review approach. The study examines various Scopus-indexed scientific publications from 2022 to 2026 that discuss aspects of financial management, including capital structure, working capital management, financial risk management, as well as the roles of corporate governance and digital transformation. The findings indicate that effective financial management practices significantly contribute to improving corporate performance in terms of profitability, firm value, and operational efficiency. Furthermore, these practices play an essential role in enhancing financial resilience in the face of economic uncertainty and global market dynamics. Digital transformation has been proven to strengthen the effectiveness of financial management through increased efficiency, accuracy, and speed in decision-making, although it also introduces new challenges related to financial risk and data security. This study highlights that the integration of optimal financial management practices, good corporate governance, and the utilization of digital technology is a key factor in achieving sustainable corporate performance and long-term financial resilience.